2015
DOI: 10.1016/j.ijpe.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Tactical supply chain planning under a carbon tax policy scheme: A case study

Abstract: Greenhouse gas emissions are receiving greater scrutiny in many countries due to international forces to reduce anthropogenic global climate change. Industry and their supply chains represent a major source of these anthropogenic emissions. This paper presents a tactical supply chain planning model that integrates economic and carbon emission objectives under a carbon tax policy scheme. A modified Cross-Entropy solution method is adopted to solve the proposed nonlinear supply chain planning model. Numerical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 48 publications
0
69
0
3
Order By: Relevance
“…For example, the effectiveness of carbon tax and emissions trading schemes on the forward operations of the supply chain have been investigated by Fahimnia et al (2014Fahimnia et al ( , 2015a and Zakeri et al (2015). Carbon taxing impacts on the forward and reverse operations of a closed-loop supply chain have also been studied by Fahimnia et al (2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the effectiveness of carbon tax and emissions trading schemes on the forward operations of the supply chain have been investigated by Fahimnia et al (2014Fahimnia et al ( , 2015a and Zakeri et al (2015). Carbon taxing impacts on the forward and reverse operations of a closed-loop supply chain have also been studied by Fahimnia et al (2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Fahimnia et al (2015) argued that instead of choosing between carbon tax and cap-and-trade system, a hybrid regulatory scheme can be investigated, and suggested that developing and comparing deterministic versus stochastic modeling efforts can examine the differences in these types of policies. Another future extension of this could be to analyse the green/low carbon warehouse management under a combination of different carbon emissions control policies, and discuss their effects on warehouse decisions and performances.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Zhang and Xu (2013) studied a singleperiod, multi-item production planning subject to a capand-trade mechanism. Later on, Fahimnia et al (2015) characterized production and allocation strategies for a carbon tax scheme. They determined insights into the carbon pricing strategy.…”
Section: Related Literaturementioning
confidence: 99%